Axial ratio enhancement of equilateral triangular-ring slot antenna using coupled diagonal line slots - Awaludin A.; Sumantyo J.T.S.; Santosa C.E.; Baharuddin M.Z. (Electromagnetics Academy, 2023)
Bandwidth; Circular polarization; Directional patterns (antenna); Electric impedance; Axial ratio bandwidth; Circularly polarized; Circularly polarized antennas; Fractional bandwidths; Impedance bandwidths; Measured results; Satellite applications; Triangular ring slot; Slot antennas